Case Report: The First Report on Moraxella canis Isolation From Corneal Ulcer in a Bulldog - Wang, Zhihao; Guo, Long; Li, Jun; Li, Jianji; Cui, Luying; Dong, Junsheng; Wang, Heng (Frontiers in Veterinary Science, 2022)
A five-year-old castrated male bulldog was diagnosed with a corneal ulcer accompanied by edema and conjunctival hyperemia. Ophthalmic examination and microbiological analysis were performed. The bacteria were gram-negative and globular. The isolated clone was identified as M. canis (MZ579539) via MALDI-TOF MS and 16S rDNA sequencing. Antimicrobial susceptibility testing showed that the bacteria were sensitive to tetracycline and chloramphenicol but resistant to levofloxacin and ciprofloxacin. After a conjunctival flap was placed, tobramycin ophthalmic solution and 5% sodium hyaluronate were administered. The ulcer was effectively controlled after surgery. After three weeks, the cornea healed. This is the first case report of a canine corneal ulcer associated with M. canis. M. canis should be considered when diagnosing the infectious agent in cases of corneal ulceration or infectious keratitis.